Advances in the noninvasive diagnosis of melanoma—40 years beyond the ABCDs - Joshua Burshtein; Alexander Witkowski; Danny Zakria; Milaan Shah; Angela Rosenberg; Lauren DeBusk; Joanna Ludzik; Giovanni Pellacani; Darrell Rigel (CA: A Cancer Journal for Clinicians, 2026)
Abstract The early detection of cutaneous melanoma is critical to survival outcomes. Because less than one half of melanomas in the United States are diagnosed by dermatologists, the ABCD (asymmetry, border irregularity, color variation, diameter >6 mm) acronym, created 40 years ago with the later addition of “E” for evolution (ABCDE), was developed for nondermatologist health care professionals and the public to simplify and enhance the diagnosis of early melanoma. It continues to be the global, naked‐eye, nondevice‐assisted standard for initial triage of pigmented lesions. This clinical review discusses the changing clinical diagnostic landscape and examines the currently available first‐line and second‐line detection modalities for melanoma. It also provides updates to the first‐line triage approach and discusses the challenges of regulatory agency oversight for the safe and effective use of current and emerging skin cancer detection technologies. It is critical that health care professionals globally have knowledge of these technologies to enhance their diagnosis of melanoma.